Proces adaptacji zapożyczeń językowych – czynniki socjo- i psycholingwistyczne wobec zróżnicowania anglicyzmów w wybranych językach słowiańskich - Warchał, Mateusz (Slavia Centralis, 2020)
The process of adapting language borrowings is realized in the following areas: didactic, glotto-didactic and translational, among other areas. A move towards establishing general language parameters concerning rules and the means and mechanisms of such adaptation is one of the practical aspects of the language analysis of borrowings. The objective of the paper is to present the processes of language borrowings, which take place on the following levels: phonological, morphological and semantic. The study has been done on the basis of selected English borrowings that are present in Slovenian, Croatian, Serbian and Bosnian.